Biparental mating in early segregating generation of aromatic rice (Oryza sativa) - KOLI, N R; PRAKASH, CHANDRA; PUNIA, S S (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was carried out during kharif 2009 to study the genetic variability created through biparental mating in the F2 of Improved Pusa Basmati 1( P 1460)×Pusa Sugandha 4 (P 1121) cross of basmati rice (Oriza sativa L.). The biparental population (BIP) had higher mean performance than the F3 self’s for all the characters under study. The lower limit of range was, in general smaller for all the characters in the biparental population. The upper limit had also increased in the desired direction for all the characters. A sufficient high genetic variation was maintained in the BIP population for most of the characters. Highest value of genetic and phenotypic coefficient of variation were recorded for grain yield/plant (34.00 and 35.21), followed by no. of spikelets/ panicle (22.05 and 23.26). Whereas, high heritability (%) and genetic advance (% as mean) were found for 1 000-grain weight (g) and panicles/m2 respectively. The utility of biparental mating in early segregating generation in aromatic rice is emphasized.